Rumex usambarensis (Dammer) Leaf and Stem Extract Effect on Body Weight and Lipid Profile: A Study in Albino Rats - Nattabi, Hilda; Nkwangu, David; Engeu Ogwang, Patrick (Journal of Pharmaceutical Research International, 2016)
The aim of the study was to determine the effect of Rumex usambarensis plant extract on body weight and lipid profile of fattened albino rats. Study Design: This was an in-vivo experimental study in laboratory animal model. Place and Duration: The study was conducted at the Faculty of Medicine, Mbarara University of Science and Technology, Uganda, from January to May 2015.Rumex usambarensis stems and leaves were collected from Kabale district in western Uganda during rainy season for the study while one whole plant was brought to the university for authentication by a university botanist. The fresh stems and leaves weighing 8.1 kg were blended in 1.045L of distilled water and filtered through a muslin cloth before evaporating in an oven set at 55°C to a constant weight of dry mass. A portion of the dry mass was screened for presence of phytochemicals groups while the remaining portion was dissolved in distilled water and administered to fattened wistar albino rats at the doses of 125 mg/kg, 250 mg/kg and 500 mg/kg corresponding to group 1, 2 and 3 respectively daily by gavage for 21 days. The Control group received equivalent volume of distilled water by gavage daily. Mean body weights at baseline and at day 21 were statistically compared using ANOVA followed by sidak statistical test at p=0.05. Lipid profiles obtained on day 21 were also compared using the same statistical tests.
Keywords: obesity; overweight; satiety; Rumex usambarensis